PENGGUNAAN BAHASA INDONESIA DIALEK MAKASSAR DALAM KEGIATAN PEMBELAJARAN DI SMA NEGERI 6 MAROS: KAJIAN SOSIOLINGUISTIK - Mustary, Mutmainnah; Iswary, Ery; Hasjim, Munira (JURNAL ILMU BUDAYA, 2018)
The research aimed to describe the forms of the code mixing, switching, and interference at State Senior High School 6 (SMAN) Maros, Bontoa District, Maros Regency, Sulawesi Selatan. This was a qualitative descriptive research examining linguistic phenomena with the sociolinguistic approach Data resource were the speeches used by the teachers of the study programs of Religious Education, Natural Science, Social Science, Physic Education, Indonesian language, mathematics, and all the speeches of the students involving in the learning process which contained the code mixing, switching, and interference. Data were collected by the non-participative observation. While the data were also collected by the scrutinized technique of the free involving conversation, recording technique, and note-taking. The classified data were then analysed by the qualitative descriptive analysis method.The research result indicates that the code mixing forms are: verb, adverb, conjunction, reduplication, personal pronouns, and phrases, whereas the code switching is in the forms of independent clauses, coordinative clauses, and sentences. and the interferences are: addition of klitika, mi, pi, ji, phoneme removal, addition of phoneme, replacement of phoneme /i/ into /e/ and phoneme /u/ to /o/. The code mixing, switching, and interference occur in the learning process at State Senior High School (SMAN) Maros, Bontoa District, Maros Regency, Sulawesi Selatan. performed by the teachers, students from Indonesian language into Makassar dialect .